2012
DOI: 10.1371/journal.pone.0050779
|View full text |Cite
|
Sign up to set email alerts
|

Screening the Budding Yeast Genome Reveals Unique Factors Affecting K2 Toxin Susceptibility

Abstract: BackgroundUnderstanding how biotoxins kill cells is of prime importance in biomedicine and the food industry. The budding yeast (S. cerevisiae) killers serve as a convenient model to study the activity of biotoxins consistently supplying with significant insights into the basic mechanisms of virus-host cell interactions and toxin entry into eukaryotic target cells. K1 and K2 toxins are active at the cell wall, leading to the disruption of the plasma membrane and subsequent cell death by ion leakage. K28 toxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 40 publications
0
37
0
1
Order By: Relevance
“…Distinct sets of host factors affecting resistance and sensitivity toward K1 and K2 killer toxins were identified, revealing functional discrepancies between these toxins as well (9,19). Analysis of the sensitivity of a ⌬kre1 mutant to either K1 or K2 toxin demonstrated total resistance in both cases, suggesting that Kre1p serves as plasma membrane receptor (19,20). Also, it was shown that both K1 and K2 bind less efficiently to a set of mutants featuring a decreased level of ␤-1,6-glucan, implying that it serves as a cell wall receptor for both proteins (9,19,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Distinct sets of host factors affecting resistance and sensitivity toward K1 and K2 killer toxins were identified, revealing functional discrepancies between these toxins as well (9,19). Analysis of the sensitivity of a ⌬kre1 mutant to either K1 or K2 toxin demonstrated total resistance in both cases, suggesting that Kre1p serves as plasma membrane receptor (19,20). Also, it was shown that both K1 and K2 bind less efficiently to a set of mutants featuring a decreased level of ␤-1,6-glucan, implying that it serves as a cell wall receptor for both proteins (9,19,20).…”
mentioning
confidence: 99%
“…The optimal pH for the action of the K2 toxin is 4.0 to 4.3 (17), somewhat lower than that of the K1 toxin, which reaches 4.6 (15,16,18). Distinct sets of host factors affecting resistance and sensitivity toward K1 and K2 killer toxins were identified, revealing functional discrepancies between these toxins as well (9,19). Analysis of the sensitivity of a ⌬kre1 mutant to either K1 or K2 toxin demonstrated total resistance in both cases, suggesting that Kre1p serves as plasma membrane receptor (19,20).…”
mentioning
confidence: 99%
“…Secondly, the use of both the K2-toxin producing strain and the purified K2 toxin in parallel increases the sensitivity of screening and allows selection of the candidates possessing even a weak phenotype. We found that 85% of mutants demonstrating a strong phenotype, confirmed by the "killer" assay, could be picked using only a K2 toxin-based "survival" assay (Servienė et al, 2012). This demonstrates that in the majority of cases, such strategy of screening could be used for the selection of marked candidates.…”
Section: Advantages Of the Use Of The Pinning Robotmentioning
confidence: 86%
“…4. The list and analysis of the aforesaid 332 mutants has been published (Servienė et al, 2012). Surprisingly, some 520 of 850 candidates discovered in the "survival" assay were missing in the "killer" assay.…”
Section: Verification Of K2 Killer Phenotypes Using the "Killer" Assaymentioning
confidence: 99%
See 1 more Smart Citation